Global Trends and Controversies in Multicultural Islamic Education within the SDGs Framework - Rosanti, Cholisa; Waston; Gigih Setianto; Yogi Muhammad Saputro; Mahnoor Fatima; Muhammad Rehan Sabi (Profetika: Jurnal Studi Islam, 2025)
Objective: This study aims to map the global development of research on multicultural Islamic education and its alignment with the Sustainable Development Goals (SDGs). It also seeks to identify trends in publication volume, key disciplines, leading countries, and emerging themes. Theoretical framework: The study uses bibliometric analysis to map the growth and trends in multicultural Islamic education research. It draws on theories of education and multiculturalism to explore how this field can help build inclusive, tolerant societies in line with the SDGs. Literature review: The literature review focuses on research in multicultural education, Islamic education, and their links to the SDGs. It highlights themes like minority groups, gender, curriculum, and pedagogy, which are central to multicultural Islamic education. It also examines prior bibliometric studies in these areas. Method: The study uses bibliometric analysis of data from the Scopus database (2000–2024). VOSviewer and Biblioshiny tools are used to analyze publication trends, disciplines, countries, and research themes, with a focus on keyword mapping and cluster analysis. Results: The research shows a significant rise in publications since 2017, peaking in 2024. The main contributions come from social sciences, humanities, and psychology. The top publishing countries are the US, UK, and Indonesia. Two main research clusters were identified: socio-demographic issues (minorities, gender) and educational policy (curriculum, pedagogy). Implications: This study highlights the potential of multicultural Islamic education as a tool for fostering inclusive, tolerant societies. It also provides a comprehensive map for future research and encourages interdisciplinary collaboration. The findings emphasize the importance of aligning this education with the global sustainable development agenda. Novelty: The novelty of this study lies in using bibliometric analysis for a topic that is typically studied qualitatively. It provides a unique, data-driven perspective and offers a global map of the field, helping to guide future research.